Blood transcriptome reveals immune and metabolic-related genes involved in growth of pasteurized colostrum-fed calves - Li, Chenglong; Li, Shuzhen; Yang, Chaoyun; Ding, Yanling; Zhang, Yanfeng; Wang, Xiaowei; Zhou, Xiaonan; Su, Zonghua; Ming, Wenxuan; Zeng, Ling; Ma, Yun; Shi, Yuangang; et al. (Frontiers in Genetics, 2023)
The quality of colostrum is a key factor contributing to healthy calf growth, and pasteurization of colostrum can effectively reduce the counts of pathogenic microorganisms present in the colostrum. Physiological changes in calves fed with pasteurized colostrum have been well characterized, but little is known about the underlying molecular mechanisms. In this study, key genes and functional pathways through which pasteurized colostrum affects calf growth were identified through whole blood RNA sequencing. Our results showed that calves in the pasteurized group (n=16) had higher body height and daily weight gain than those in the unpasteurized group (n=16) in all months tested. Importantly, significant differences in body height were observed at 3 and 4 months of age (p < 0.05), and in daily weight gain at 2, 3, and 6 months of age (p < 0.05) between the two groups. Based on whole blood transcriptome data from 6-months old calves, 630 differentially expressed genes (DEGs), of which 235 were upregulated and 395 downregulated, were identified in the pasteurized compared to the unpasteurized colostrum groups. Most of the DEGs have functions in the immune response (e.g. CCL3, CXCL3, and IL1A) and metabolism (e.g. PTX3 and EXTL1). Protein-protein interaction analyses of DEGs revealed three key subnetworks and fifteen core genes, including UBA52 and RPS28, that have roles in protein synthesis, oxidative phosphorylation, and inflammatory responses. Twelve co-expression modules were identified through weighted gene co-expression network analysis. Among them, 17 genes in the two modules that significantly associated with pasteurization were mainly involved in the tricarboxylic acid cycle, NF-kappa B signaling, and NOD-like receptor signaling pathways. Finally, DEGs that underwent alternative splicing in calves fed pasteurized colostrum have roles in the immune response (SLCO4A1, AKR1C4, and MED13L), indicative of potential roles in immune regulation. Results from multiple analytical methods used suggest that differences in calf growth between the pasteurized and unpasteurized groups may be due to differential immune activity. Our data provide new insights into the impact of pasteurization on calf immune and metabolic-related pathways through its effects on gene expression.